2015
DOI: 10.1094/pdis-09-14-0989-re
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pathogenic Variation among Phakopsora pachyrhizi Isolates Collected from the United States and International Locations, and Identification of Soybean Genotypes Resistant to the U.S. Isolates

Abstract: A major constraint in breeding for resistance to soybean rust has been the virulence diversity in Phakopsora pachyrhizi populations. In greenhouse experiments, reactions of 18 soybean genotypes to 24 U.S. isolates from 2007 and 2008 and 4 foreign isolates were compared. Reactions of four differentials (Rpp1 to Rpp4) to these U.S. isolates were also compared with reactions to nine foreign isolates and three U.S. isolates from 2004. Principal component analysis (PCA) of the reaction types grouped the U.S. isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 50 publications
1
40
2
Order By: Relevance
“…The US isolates expressing the same pathogenicity profile as US isolates collected in 2004 when soybean rust was first found in the US (Schneider et al 2005), have not been detected in subsequent US samples (Paul et al 2015, Paul & Hartman 2009, Pham et al 2009). Therefore, it has been suggested that P. pachyrhizi isolates existing in 2004 disappeared or were suppressed due to the subsequent winter, likely resulting in unfavorable conditions for pathogen survival a resistant reaction in response to 5%-53% of the rust populations.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The US isolates expressing the same pathogenicity profile as US isolates collected in 2004 when soybean rust was first found in the US (Schneider et al 2005), have not been detected in subsequent US samples (Paul et al 2015, Paul & Hartman 2009, Pham et al 2009). Therefore, it has been suggested that P. pachyrhizi isolates existing in 2004 disappeared or were suppressed due to the subsequent winter, likely resulting in unfavorable conditions for pathogen survival a resistant reaction in response to 5%-53% of the rust populations.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this paper, coupled with Akamatsu et al (2013), describes the pathogenicity of the largest P. pachyrhizi collection, consisting of populations from eight cropping seasons from 2007 to 2015 in three South American countries. (Paul et al 2015, Paul & Hartman 2009). In this study, a highly virulent Argentinean population (i.e., ANE6-6) was discovered, and it could pose a serious threat since none of the Rpp-carrying differentials demonstrated a resistant reaction to the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI 200492 was immune or resistant by inoculation to isolates collected in India in 1973, Australia in 1979, and Hawaii in 1994and 1989. However, this variety produced TAN reactions to isolates collected in Taiwan in 1972and 1980, and in Thailand in 2001 (Bromfield 1984, Bonde et al 2006, Pham et al 2009, Ray et al 2009, Paul et al 2015. In Japan, although the majority of soybean and kudzu (Pueraria lobata) isolates collected from 1993 to 1997 induced susceptible reactions on PI 200492 (Yamaoka et al 2002), isolates collected in 2007 to 2009 induced resistance reactions (Yamaoka et al 2014).…”
Section: Major Resistance Genes To Soybean Rustmentioning
confidence: 99%
“…In Africa, PI 200492 produced TAN reactions by inoculation with isolates collected in Zimbabwe and South Africa in 2001 (Bonde et al 2006, Pham et al 2009, Ray et al 2009, Paul et al 2015. In Uganda, low disease severity was observed in field trials conducted in (Oolka et al 2008.…”
Section: Major Resistance Genes To Soybean Rustmentioning
confidence: 99%